Structure and properties of polyethylene terephthalate treated by supercritical CO2 - Gao Shi-Hui (Thermal Science, 2018)
Structure and properties of polyethylene terephthalate were characterized by SAM, Fourier transform infrared spectrometry, X-ray diffraction, and thermal analysis to evaluate the effect of supercritical CO2 on the structural behavior. The dynamic shrinking behavior of polyethylene terephthalate was analyzed using the Kelvin-Voigt model. The results indicated that uneven and significantly different surface of the polyethylene terephthalate fiber was displayed since the spinning oil and other additives added in spinning process were rinsed in super-critical CO2. The slight shifts for the characteristic bands of polyethylene terephthalate in Fourier transform infrared spectrometry were observed due to some re-arrangements and recrystallizations of the molecule chains after supercritical CO2 treatment. Simultaneously, the crystallinities and the fastest thermal decomposition temperatures of polyethylene terephthalate were improved slightly from 80°C to 120°C in supercritical CO2. Furthermore, the shrinkage of the treated polyethylene terephthalate samples was increased gradually from 2.73% to 3.35% with the temperature raising.